Active Learning as a Strategy for Internalizing Islamic Values in PAI Learning at High Schools - Hilabi, Abdurrahman; Fatah, Abdul; Nurmalina, Nurmalina (Jurnal Simki Postgraduate, 2025)
This study aims to analyze the integration of the active learning method in strengthening Islamic values within Islamic Religious Education (PAI) at SMA PGRI Padang Cermin, in response to the gap between students’ cognitive understanding and the practical implementation of religious values. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the PAI teacher and students, classroom participatory observations, and document analysis of syllabi, lesson plans, and students’ reflective journals. The participants consisted of one PAI teacher and 32 tenth-grade students. Data analysis was conducted using the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing and verification. The findings revealed four major themes: the expansion of dialogical participation, the internalization of values through authentic experiences, the integration of cognitive, affective, and psychomotor domains, and supporting and inhibiting factors in implementation. Discussion-based learning, simulations, and collaborative projects were found to facilitate moral reflection and the enactment of Islamic values such as honesty, responsibility, empathy, and cooperation. This study reinforces the constructivist perspective in value education and offers practical implications for instructional design and character-based assessment policies. Future longitudinal research is recommended to examine the sustainability of value internalization over time.